Question
Asked Oct 24, 2019
3 views
x+6
lim
x--6t x+ 6
lim
x6 x6
Jx 6
lim
x6 x6
=
help_outline

Image Transcriptionclose

x+6 lim x--6t x+ 6 lim x6 x6 Jx 6 lim x6 x6 =

fullscreen
check_circle

Expert Answer

star
star
star
star
star
1 Rating
Step 1

If x-> -6^+ then x>-6

That means x+6>0

So, |x+6|=x+6

Answer(a): limit x-> -6^+ |x+6|/(x+6)= 1 

help_outline

Image Transcriptionclose

|X+61 lim X6X6 .-6+ х-— x+6 = lim x--6+ =1

fullscreen
Step 2

If x-> -6^- then x<-6

That means x+6<0

So, |x+6|=-(x+6)

Answer(b): ...

help_outline

Image Transcriptionclose

x+6 lim x-6X6 -(x+6) = lim x6X+6 =-1

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Calculus

Other